Triple therapy revolutionizes treatment paradigms for previously untreatable HCC complicated by high-flow hepatic arteriovenous fistulas - Jinpeng Li; Jinpeng Li; Yuanming Li; Jingtao Zhong; Jiasheng Du; Jiao Chen; Jutian Shi; Lujun Zhao; Jinlong Song (Frontiers in Immunology)
PurposeTo evaluate the short-term efficacy and safety of hepatic arterial infusion chemotherapy (HAIC) combined with immune checkpoint inhibitors (ICIs) and tyrosine kinase inhibitors (TKIs) in patients with hepatocellular carcinoma (HCC) complicated by high-flow hepatic arteriovenous fistula (HAVF).Patients and methodsWe retrospectively analyzed clinical data from 40 patients with unresectable HCC complicated by high-flow HAVF who received FOLFOX regimen HAIC plus ICIs and TKIs between January 2021 and June 2023. The efficacy evaluation included HAVF effective rate, tumor response, progression-free survival (PFS), overall survival (OS) per RECIST 1.1 and mRECIST. Adverse events (AEs) were recorded for safety evaluation.ResultsThe median follow-up time was 10.5 months (range: 3.5-16.4 months). A total of 150 HAIC cycles were administered, with a median frequency of 3.8 cycles per patient. The objective response rate (ORR) and the disease control rate (DCR) was 42.5% and 92.5% according to the RECIST 1.1, and 75.0% and 92.5% according to mRECIST criteria, respectively. The median PFS and the median OS were 5.5 months (95% CI: 3.9-6.9) and 10.4 months (95% CI: 7.4-13.4), respectively. In univariate analysis, HAVF grade, extrahepatic spread, HAVF disappearance were potential prognostic factors for OS, while HAVF grade and extrahepatic spread being independently associated with PFS. Hypertension (12.5%), Thrombocytopenia (12.5%) and Albumin decreased (7.5%) were the most frequently observed grade 3-4 TRAEs.No treatment-related mortality occurred during the study period.ConclusionHAIC combined with ICIs and TKIs demonstrates promising short-term efficacy and acceptable safety in patients with unresectable HCC complicated by high-flow HAVF. This combination therapy effectively controls tumor growth while simultaneously managing the arteriovenous shunt, providing a valuable treatment option for this challenging patient population.